Editorial - Barney, Katelyn; Nakata, Martin (The Australian Journal of Indigenous Education, 2017)
We are very pleased to bring you Volume 46 of The Australian Journal of Indigenous Education. This year is a particularly significant time for Aboriginal and Torres Strait Islander issues and education. It marks the 25th anniversary of the landmark Mabo decision that refuted the legal doctrine of terra nullius and recognised that the Miriam people were continuously present and exclusively possessed Mer in the Torres Strait. It is also the 50th anniversary of the 1967 referendum, a significant milestone resulting in constitutional change to recognise Aboriginal and Torres Strait Islander peoples in the national census. This year also marks the release of the Universities Australia Indigenous Strategy 2017–2020, which is designed to provide a sector-wide initiative that binds all universities together with common goals. The strategy includes important initiatives to increase the numbers of Aboriginal and Torres Strait Islander people participating in higher education, increase the engagement of non-Indigenous people with Indigenous knowledge and educational approaches, and improve the university environment for Aboriginal and Torres Strait Islander people.